Breast Cancer Vaccines: Disappointing or Promising? - Zhu, Si-Yuan; Yu, Ke-Da (Frontiers in Immunology, 2022)
Breast cancer has become the most commonly diagnosed cancer globally. The relapse and metastasis of breast cancer remain a great challenge despite advances in chemotherapy, endocrine therapy, and HER2 targeted therapy in the past decades. Innovative therapeutic strategies are still critically in need. Cancer vaccine is an attractive option as it aims to induce a durable immunologic response to eradicate tumor cells. Different types of breast cancer vaccines have been evaluated in clinical trials, but none has led to significant benefits. Despite the disappointing results at present, new promise from the latest study indicates the possibility of applying vaccines in combination with anti-HER2 monoclonal antibodies or immune checkpoint blockade. This review summarizes the principles and mechanisms underlying breast cancer vaccines, recapitulates the type and administration routes of vaccine, reviews the current results of relevant clinical trials, and addresses the potential reasons for the setbacks and future directions to explore.